Teacher-Assessed Mi-Robot Training Improves Linguistic and Kinesthetic Stimulation for Children with Special Needs - Taryudi Taryudi; Wisnu Djatmiko; Murti Kusuma; Linlin Lindayani (Universitas Bumigora, 2026)
The increasing need for effective learning support for children with special needs highlights the urgency of integrating assistive technologies that enhance linguistic and kinesthetic stimulation and support teachers in instructional delivery. Conventional methods often struggle to provide consistent and engaging stimulation, particularly in digital or distance learning contexts. The objective of this study was to evaluate teachers’ acceptance and perceived usefulness of the Mi-Robot for linguistic and kinesthetic stimulation. This research method is a descriptive mixed-methods study involving 20 special education teachers from 5 elementary schools in Bandung, Indonesia. Teachers received structured training in the use of Mi-Robot. Data were collected using the Mi-Robot Acceptance Scale based on the Technology Acceptance Model and an open-ended usability evaluation form. The results indicate that Mi-Robot aligns with the school curriculum and demonstrates high perceived usefulness, ease of use, positive attitudes, and strong behavioral intentions among teachers. Qualitative findings indicate that Mi-Robot effectively supports linguistic and kinesthetic stimulation through its content, functionality, and cost-effectiveness. In conclusion, Mi-Robot demonstrates strong potential as an assistive educational technology for special education in both classroom and distance-learning settings.